PENGARUH KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI BANK SYARIAH X KANTOR WILAYAH II - Deden Misbahudin Muayyad; Ade Irma Oktafia Gawi (Jurnal Manajemen dan Pemasaran Jasa, 2016)
The title of this study is the effect of job satisfaction on employee productivity Islamic Bank X regional office II. The purpose of this study was to determine the average job satisfaction and employee productivity Isalmic Bank X regional office II; to determine whether there is influence of job satisfaction on employee productivity; and the extent of their influence. The research design used is a combination of descriptive and causal by the number of respondents as many as 35 people. Results of this study was the average level of employee satisfaction at Bank Syariah X Regional Office II is quite satisfied, while the average level of productivity of employees included in the category productive. Then there is no significant effect of job satisfaction on employee productivity with regression equation Y = 66.788 + 0,357X. The magnitude of the effect of job satisfaction on employee productivity is at 7.5%, while the remaining 92.5% is influenced by other variables not included in this model.